Inclusive Growth, Institutions, and the Underground Economy - Mohommad, Adil (IMF Working Papers; Working Paper ;, 2012)
Worldwide protests against the perceived lack of economic opportunity and failure of governance have refocused attention on the need for inclusive growth and strong institutions. In developing countries, large informal economies limit state capacity to deliver governance and strong institutions, which in turn discourages participation in and expansion of the formal economy. This paper analyzes the determinants of the underground economy, with particular emphasis on the role of institutions and the rule of law. We find that when businesses are faced with onerous regulation, inconsistent enforcement and corruption, they have an incentive to hide their activities in the underground economy. Empirical analysis suggests that institutions are a more important determinant of the size of the underground economy than tax rates.